2006
DOI: 10.1038/sj.bjc.6603265
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose-finding and pharmacokinetic study of subcutaneous semisynthetic homoharringtonine (ssHHT) in patients with advanced acute myeloid leukaemia

Abstract: To determine the maximum-tolerated dose (MTD), dose-limiting toxicities and pharmacokinetic of semisynthetic homoharringtonine (ssHHT), given as a twice daily subcutaneous (s.c.) injections for 9 days, in patients with advanced acute leukaemia, 18 patients with advanced acute myeloid leukaemia were included in this sequential Bayesian phase I dose-finding trial. A starting dose of 0.5 mg m À2 day À1 was explored with subsequent dose escalations of 1, 3, 5 and 6 mg m À2 day À1 . Myelosuppression was constant. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…Although this drug has activity as a single agent in hematologic malignancies (40,41), it did not reduce the size of established solid tumors in clinical studies (42,43). Our report might provide an explanation for the lack of benefit of homoharringtonine in solid tumors.…”
Section: Discussionmentioning
confidence: 72%
“…Although this drug has activity as a single agent in hematologic malignancies (40,41), it did not reduce the size of established solid tumors in clinical studies (42,43). Our report might provide an explanation for the lack of benefit of homoharringtonine in solid tumors.…”
Section: Discussionmentioning
confidence: 72%
“…19 In a clinical trial in hematologic malignancies the maximal tolerated dose of HHT administered subcutaneously in AML was 5 mg/m 2 /day for 9 days, which generated mean peak plasma concentration of 96.1 Ϯ 20.3 ng/mL (176 Ϯ 37nM). 40 In CML clinical trials, the total dose of HHT used was 2.5 mg/m 2 /day, administered by subcutaneous injection twice daily for 7-14 days. This was well tolerated in each study and was subsequently shown to be active in patients with the T315I mutation of Bcr-Abl.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Dans cet essai, cinq niveaux de dose étaient prévus au départ, et la dose maximale tolérée (5 mg.m −2 /jour soit le quatrième niveau de dose) a été définie après l'inclusion de 18 patients évaluables par cohortes de trois.…”
Section: Essais De Phase 1 De Recherche De Doseunclassified